Heat transfer and irreversibility analysis of magnetic nanomaterial within corrugated enclosure. (July 2020) - Xu, Xiaowei; Qi, Cong; Shafee, Ahmad; Vuong, Bui Xuan
Abstract: Free convention of nano liquid with considering hybrid nanoparticles through a chamber with wavy inner surface is scrutinized and non-Darcy technique is applied for permeable region modeling. Not only thermal analysis but also components of irreversibility are presented in outcomes which are obtained via CVFEM. Employing homogeneous model of nanomaterial let us to use benefits of previous formulation based empirical researches. As a good output, we suggested new formulations for significant functions which help the readers to find the values of functions in ranges of parameters which studied in current article. Results indicate that as magnetic field imposed, thicker boundary layer obtains and leads to lower Nuave . A growth of permeability leads to easer nanomaterial flow and thinner boundary layer. Increase of Lorentz forces characterizes reduction of convective flow of nanomaterial but no sensible changes was reported for Be with changing Ha .